Understanding the Socio-Cultural Context of Bodily Management and the Phenomenon of Emulation of Female Cinema Stars in Iran: A Case Study of Women Attending Clinics in District 5, Tehran - zeinab ebrahimi; Zahra Ghasemi (مطالعات رسانه‌های نوین, 2023)
IntroductionWith the shift from traditional to modern society, significant socio-cultural transformations have brought about remarkable transformations in both the concept of the body and related approaches. Body management practices have evolved into a whole new dimension that has experienced profound alterations. These transformations are so profound that they have given rise to a scientific domain solely devoted to the study and understanding of the concept of body management. Modern society is teeming with vast amounts of data pertaining to the body, spurring social researchers to delve into the intriguing domain of body management patterns. These studies, undertaken over the last few decades, have led to a myriad of investigations centered upon this very theme.Within contemporary societies, female cinema stars occupy a highly sought-after and idealized position in the sphere of body management. The cinema industry harnesses the power of women and men who exude specific fashion trends with the aim of captivating audiences and amassing profits. The principal objective of this research is to investigate to what extent women residing in Tehran emulate the body management practices employed by female cinema stars.MethodologyThe study in question adopts a qualitative methodology known as Grounded Theory, which brings together the Paradigmatic Model of Strauss and the Constructing Grounded Theory Model proposed by Kathy Charmaz. Utilizing this approach, this research employs tools such as in-depth interviews and observation for data collection, which are developed and fine-tuned as the study unfolds.For this study, the targeted participants are women who receive treatment in beauty clinics situated in District 5 of Tehran. To select participants, the study employs two sampling methods: purposive non-probability sampling and theoretical sampling. The sample size is deliberately chosen to be sufficiently large in order to achieve theoretical saturation, meaning that the sampling process persists until no significant new insights are gained from adding additional samples to the study.During the data categorization and coding process, the initial step involves extracting phrases, explanations, sentences, and signaling words or phrases, as they serve as evidence that the interviewees have attempted to differentiate and label their body management practices, or to give further explanation on their body-related behaviors. This process is conducted through an open coding approach, which means that no rigid classification is imposed on the data and that the classifications emerge organically from the data itself.Subsequently, the identified codes are combined based on shared semantic themes. Afterwards, based on common features of grouped phrases within each theme, a hierarchical process is undertaken to unveil related themes, essential patterns, and ultimately, central themes. In the final phase of this research, the extracted themes are compared to the portrayal of female cinema stars' body management styles in their movies and on social media.FiningsThe target population of this research consists of 14 female participants, ranging between 17 to 68 years old, who have undergone at least one cosmetic surgery on different parts of their face and body. All participants in this study have chosen to undergo cosmetic surgery of their own accord. The primary model derived from this research aims to explore the sociological aspects of body management and the process of pattern replication in Iranian cinema, as seen in the case of female cinema stars.The data analysis process has employed open coding and axial coding methodologies suggested by the Paradigmatic Model of Strauss and Constructing Ground Theory Model proposed by Kathy Charmaz, where open coding was applied as the first step, followed by axial coding as the second step.A total of 25 axial codes were ultimately extracted. These codes were subsequently grouped into four overarching categories: antecedent conditions, facilitating conditions, interventions, and outcomes and strategies, as well as consequences.Causal conditions encompass events and situations that precede and contribute to the emergence of specific phenomena. These causal conditions are generally classified into four main categories:Causative Conditions: Events or circumstances that precipitate an event. Causative conditions are typically grouped into four primary categories. A significant antecedent condition influencing the decision to undergo cosmetic surgery is the media's competitive nature.Contextual Conditions: A set of characteristics that are closely associated with a particular phenomenon, reflective of the setting in which the event occurs. Antecedent and facilitating factors influencing the rise in cosmetic surgery rates encompass social pressures. These pressures are significant elements within the broader context where interventions take place.Intervening Conditions: Interventions involve procedures, practices, or strategies implemented to handle, control, or respond to a phenomenon. Several survey participants resort to cosmetic surgery as a strategy to garner attention and prominence.4. Outcomes and Strategies: This category pertains to the outcomes, outputs, or consequences of actions and responses. These encompass increased social acceptance, reduced political and social engagement, elevated self-confidence, coping with aging issues, higher chances of success, amplified social stature, augmented income through social networks, aesthetic preferences, and the fulfillment of beauty standards.ResultsSocial competition for beauty does not merely exist in the real world but is also amplified in the perceptions of female audiences through a form of media-induced competition. In essence, the competition for beauty is solidified within a reciprocal and dynamic relationship between the media and the social world. Cultural and social patterns, such as spiritual ownership, symbolic competition, and extravagant consumption, significantly influence individuals' media consumption and consequent interpretations.Actresses featured in both national and international media function as representatives of other social actors who serve as points of interest and competition in the realm of cosmetic surgery discourse. Some individuals tend to fixate solely on actresses' facial beauty, while overlooking other aspects of their appearance and character. Another significant causal condition is the negative perception of one's body, which is fostered by the media's influence. Discontent with one's life and the perception of certain problems as irreversible contribute significantly as antecedent factors that can lead to the decision to undergo cosmetic surgery.Furthermore, the progress of medical science has significantly contributed to the phenomenon of cosmetic surgery, as the media has allowed cultural and social acceptance of this trend. Concurrently, advances in medicine have made it easier than ever to satisfy these desires and cater to individuals' aesthetic goals. The trend of imitating the cosmetic surgery procedures of movie stars can be observed through the use of several strategies: garnering public attention, concealing one's true self, increasing social media followership, and closely monitoring and controlling one's body.